2021
DOI: 10.1186/s12544-020-00468-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the phantom jam externality: the case of an Autobahn section in Germany

Abstract: If not restricted by tolls, private decisions to drive on a highway result in inefficiently high usage which leads to traffic jams. When traffic demand is high, traffic jams can occur simply because of the interaction of vehicle drivers on the road, a phenomenon called phantom jam. The probability of phantom jams occurring increases with traffic flow. Unpriced externalities lead to inefficiently high road usage. We offer a method for quantifying traffic jam externalities and identifying and isolating the phant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…There is also a danger of suspension destruction in connection with a sudden body descent that can be a reason for a car accident, as also given in publication 11 in which the authors concluded that the axle road is the main cause of heavy weight vehicles' malfunctions on highways in Poland, and then there is an increased risk of congestions due to obstructions, which is a frequent phenomena on the highways. Thus, the axle load has a negative impact on the economics, air quality as well as supply chains [12][13][14] . The axle load is also connected with a breach of legislation, and it could happen when the maximum permissible vehicle mass is not exceeded as well 15 .…”
Section: Consequences Of Load Distribution In Selected Vehicles In Th...mentioning
confidence: 99%
“…There is also a danger of suspension destruction in connection with a sudden body descent that can be a reason for a car accident, as also given in publication 11 in which the authors concluded that the axle road is the main cause of heavy weight vehicles' malfunctions on highways in Poland, and then there is an increased risk of congestions due to obstructions, which is a frequent phenomena on the highways. Thus, the axle load has a negative impact on the economics, air quality as well as supply chains [12][13][14] . The axle load is also connected with a breach of legislation, and it could happen when the maximum permissible vehicle mass is not exceeded as well 15 .…”
Section: Consequences Of Load Distribution In Selected Vehicles In Th...mentioning
confidence: 99%
“…However, due to the rapidly increasing in car ownership and the concerns of global warming, negative externalities brought by highway infrastructures, such as congestion, accidents, air pollution, and noise, are widely criticized. In the realm of mobility, the increasing severity of traffic congestion and the increasing number of accidents have increased the transportation cost and safety cost of residents [51,52]. For example, traffic congestion costs the United Kingdom economy an estimated ₤6.9 billion a year in lost time in 2019 [58].…”
Section: ) Evaluation Indicators In the Social Dimensionmentioning
confidence: 99%